FEATURES OF THE 24-HOUR BLOOD PRESSURE PROFILE IN PATIENTS WITH ARTERIAL HYPERTENSION AND VARIOUS CARDIAC RHYTHM DISORDERS - Nuritdinova N. Batirovna; Shaolimova Z. Mirabitovna (Web of Journals Publishing, 2025)
The aim of the study is to analyze the characteristics of the 24-hour blood pressure (BP) profile in patients with arterial hypertension (AH) complicated by various cardiac rhythm disorders. The interrelationships between the type of arrhythmia and the parameters of 24-hour blood pressure monitoring (ABPM) are examined.
Keywords: Arterial hypertension, cardiac rhythm disorders, 24-hour blood pressure profile, variability, ABPM.